Acute enhancement strategies for countermovement jump performance: a network meta-analysis of different resistance training protocols - Zhou, Ying; Wen, Kaiming; Sun, Yulong (Frontiers in Physiology, 2026)
BackgroundCountermovement jump performance is the gold standard for assessing lower limb power, and even minor improvements can significantly enhance performance in sports such as basketball and volleyball. Post-activation potentiation (PAP) and post-activation performance enhancement (PAPE) are key mechanisms for acute performance enhancement, but the relative efficacy of different resistance training protocols (such as squats, deadlifts, flywheel training, and leg presses) remains unclear.ObjectiveTo quantify and rank the acute potentiating effects of four resistance training protocols (conventional squats, flywheel squats, deadlifts, and leg presses) on countermovement jump performance through a network meta-analysis, and to explore the optimal load intensity and rest interval for the best resistance training modality.MethodsSix major databases were searched (up to May 2025), and 51 randomized controlled trials (involving 886 athletes) were included. A network meta-analysis within a frequentist framework was conducted, with standardized mean differences (SMD) and surface under the cumulative ranking curve (SUCRA) used to assess the efficacy ranking. Subgroup analyses were performed based on load intensity (≥85% 1RM for high intensity, <85% 1RM for moderate-low intensity) and rest interval (short: 0–4 min; medium: 5–7 min; long: ≥8 min).ResultsA total of 51 studies were included. Flywheel training had the highest SUCRA value (95.8%), with a significant improvement in countermovement jump performance (SMD = 0.67, 95% CI: 0.22–1.12). This was followed by deadlifts (SUCRA = 62.4%, SMD = 0.28, 95% CI: 0.22%-0.78%) and back squats (SUCRA = 57.6%, SMD = 0.23, 95% CI: 0.03%-0.48%). Leg presses may have a negative impact on countermovement jump performance (SUCRA = 9.4%, SMD = −0.36, 95% CI: 1.18%-0.45%). For flywheel training, the best results were observed with moderate intensity (SMD = 0.92, 95% CI: 0.05%–1.80%) and medium rest intervals (SMD = 0.96, 95% CI: 0.04%–1.87%).ConclusionBased on evidence of high quality level, Flywheel training is the best way to enhance acute countermovement jump performance. Regarding training parameters, while subgroup analyses point towards moderate intensity and 5–7 min of rest, these should be viewed as preliminary indicators due to wide confidence intervals and residual heterogeneity. While the conclusions for deadlifts and squats are based on less conclusive evidence, they are recommended as alternative options when a flywheel device is not available. If conditions do not permit, deadlifts can be considered as the next best option. However, the current evidence is insufficient to support the positive role of leg press in enhancing acute jumping ability.